Pt‐V2O5/NT and Pt‐WO3/NT Titanate Nanotubes with Strong Photocatalytic Activity under Visible Light. Issue 3 (22nd January 2019) - Camposeco, Roberto; Castillo, Salvador; Hinojosa‐Reyes, Mariana; Rodriguez‐Gonzalez, Vicente; Nava, Noel; Mejía‐Centeno, Isidro
Abstract: Photocatalytic degradation of Rhodamine B was carried out by decorated V2 O5 /NT and WO3 /NT titanate nanotubes with Pt (0.3 wt. %) under visible light irradiation. The effect of parameters such as titanic acid phase, surface area and photocatalyst load on the deactivation of the photocatalytic degradation of Rhodamine B were studied. Photoatalysts were characterized by SBET, XRD, UV‐vis, XPS, HR‐TEM, and H2 ‐TPR. We found that Pt‐WO3 /NT photocatalyst reached 90% of dye degradation in 60 min. WO3 /NT reached 60% after 90 min under 450‐nm visible light irradiation and pH neutral. The incorporation Pt nanoparticles into WO3 /NT and V2 O5 /NT supports increased remarkably the photocatalytic activity during degradation of Rhodamine B. After reaction, an evolution from VO2 to V2 O5 was observed. We also found the transition from W 5+ to W 6+ . The transition from Pt 0 to Pt 2+ was also observed. We concluded that the presence of Pt hinders the oxidation of the oxygen species on the surface of the titanate nanotubes. Abstract : Addition of Pt nanoparticles enhances the reduction process from V 5+ to V 4+ and V 3+ for Pt‐V2 O5 /NT and from W +6 to W +5 on Pt‐WO3 /NT photocatalyts. After 60 min of reaction under visible light, Pt hinders the oxidation process of V and W to promote the conversion of Rhodamine B.